The social profitability of rural roads in a small open economy: Do urban agglomeration economies matter? - Clive Bell (Papers in Regional Science, 2022)
The effects of a rural roads programme depend on labour mobility, how the programme is financed, and agglomeration economies. If financed by a rural poll tax and cross-price effects and agglomeration economies are sufficiently small, the wage will rise, with some return migration. Taxes on trade act as countervailing distortions, yielding urban households some relief. Rural-urban commuting promotes the exploitation of agglomeration economies; taxes on international trade are then inferior to a poll tax. The change in the value, at producer prices, of the rural sector's net supply vector can be a poor measure of the programme's social profitability.
Keywords: 300; rural roads; social profitability; transport costs; agglomeration economies; small open economy